If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 125 + -4x = 41x + 15 Reorder the terms: 125 + -4x = 15 + 41x Solving 125 + -4x = 15 + 41x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-41x' to each side of the equation. 125 + -4x + -41x = 15 + 41x + -41x Combine like terms: -4x + -41x = -45x 125 + -45x = 15 + 41x + -41x Combine like terms: 41x + -41x = 0 125 + -45x = 15 + 0 125 + -45x = 15 Add '-125' to each side of the equation. 125 + -125 + -45x = 15 + -125 Combine like terms: 125 + -125 = 0 0 + -45x = 15 + -125 -45x = 15 + -125 Combine like terms: 15 + -125 = -110 -45x = -110 Divide each side by '-45'. x = 2.444444444 Simplifying x = 2.444444444
| (n-4)*2=10 | | 5a+7=32 | | 2x+17=10x-37 | | 7x-0.05-2x=3.15 | | -16n+12-14n=-8 | | 12t+35-2t=20 | | 12+35-2t=20 | | 4a-3=2 | | 11x+2=-20 | | 6x^2-6x-11655=0 | | 5(1+x)=2(x-5) | | 14-3*(3-3x)=50 | | 5x-(-15-4x)+16=-14 | | 8x+(-7-5x)+25=-9 | | 3-8*(2+4x)=19 | | 3-8*(2+5x)=19 | | 5x-(-9+2x)+16=4 | | 4x+(-14+5x)+23=63 | | 17+4*(5-5x)=-23 | | 3x-(4-5x)+23=-37 | | 5x+(14+2x)+11=-31 | | 10+2*(3+3x)=46 | | 6x-(3x+6)+20=38 | | 2x+(4x+12)+3=21 | | 2=9-a | | x+2=.5(3x+11) | | 15=4a-3 | | =a+a^2b+a^3b^3 | | =28a^2b^2c^2+21a^2bc^2-14abc | | P=20-2Q | | =2m^3n^2-16m^2n^3+8mn | | =36p^2q^2-12pq |